ANALISIS PERAN SEKTOR INDUSTRI KREATIF TERHADAP PENYERAPAN TENAGA KERJA DI INDONESIA - Hesty Aisyah; Yopi Eka Anroni (Procuratio : Jurnal Ilmiah Manajemen, 2018)
This study aims to analyze the role of creative industry sector in the absorption of manpower in the State of Indonesia from 2002 to 2010. Research variables are divided into two, namely the dependent variable (employment absorption) and independent variables (number of firms, total expenditure for labor, and workforce). Then the data used in this research is obtained from secondary data of one of the statistical institutions in Indonesia namely the Central Statistics Agency of West Sumatra Province which has been compiled and summarized in a book "Indonesia In Figures from the Year 2002-2010". The analytical method used is Ordinary Least Square (OLS). The research finds that the creative industry has been well developed and has a positive impact on the Indonesian economy, as evidenced by the contribution of the creative industry sector to the Indonesian economy of 7.74% from the range of 2002-2010. Then two of the three independent variables, namely the number of companies and the number of labor force have a positive effect on the absorption of workers in Indonesia. Penelitian ini bertujuan untuk menganalisis peranan sektor industri kreatif dalam penyerapan tenaga kerja di Negara Indonesia dari tahun 2002 sampai dengan 2010. Variabel penelitian terbagi dua, yaitu variabel dependen (penyerapan tenaga kerja) dan variabel independen (jumlah perusahaan, jumlah pengeluaran untuk tenaga kerja, dan angkatan kerja).Kemudian data yang digunakan dalam penelitian ini didapat dari data sekunder salah satu lembaga statistik di Indonesia yaitu Badan Pusat Statistik Provinsi Sumatera Barat yang telah disusun dan dirangkum dalam sebuah buku “Indonesia Dalam Angka dari Tahun 2002- 2010”. Metode analisis yang digunakan adalah Ordinary Least Square (OLS). Hasil penelitian menemukan bahwa Industri kreatif sudah dikembangkan dengan baik dan telah berdampak positif bagi perekonomian Indonesia, terbukti dengan kontribusi sektor industri kreatif terhadap perekonomian Indonesia sebesar 7,74% dari rentang tahun 2002-2010. Kemudian dua dari tiga variabel independen yaitu jumlah perusahaan dan jumlah angkatan kerja berpengaruh positif terhadap penyerapan tenaga kerja di Indonesia.